Development of Alternaria blight resistant lines through interspecific hybridization between Indian mustard (Brassica juncea L.) and white mustard (Brassica alba) through embryo rescue (Journal of Oilseed Brassica, 2026)
Wide hybridization is an important technique for incorporation of desirable characters among related species of plants. In the present study, interspecific hybridization was carried out through in vitro culture of ovules from the crosses between Brassica juncea (cv. RH30, RH8812, RH270 and RH345) and B. alba for purpose of transferring Alternaria blight resistance from B. alba to B. juncea. Ovules were excised from siliquae and cultured on seven different MS modified media. In all crosses, the hybrid siliquae were shorter in length than their parent plants due to interspecific hybridization barriers. Pod setting in hybrid plants ranged from 39 to 48% and number of ovules per pod were also very few. Best germination response was observed in ovules used from 20 DAP on basal medium supplemented with Kin (2.5 mg/l) and CH (0.5 g/l) (for cv. RH30 x B. alba) and MS + BAP (2.5 mg/l) + CH (0.5 mg/l) (for other crosses). Six rooting media were tried for root formation in regenerated shoots. Maximum rooting response was on MS medium supplemented with IAA (0.5 mg/l) in all hybrids. The regenerated hybrid plants were transferred to a mixture of sand: soil in 1:1 ratio in pots and about 70 percent hybrid plants for all the crosses were survived. Successful hybrid plants were grown in field upto F7 generations. Advanced generation progenies were also successfully confirmed using molecular marker analyses for Alternaria blight resistance character. In advanced generation, the hybrid plant’s characteristics were comparable to their Indian mustard parent plants and they were highly resistant to Alternaria blight disease.